Trending Topics About Performance in Second Language Learning - Peña-Acuña, Beatriz (Lesya Ukrainka Eastern European National University, 2023)
This article recomposes the background of this theme during the decade 2001 to 2011. This study aims to discover ten main current research trends of performance in second language from 2012 to 2022. It will search scientific articles in the Social Science Citation Index (WOS) and in the Educational Resources Information Center (ERIC) databases and discover which are emergently compared to the previous decade. Finally, the study discusses these topic trends, other alternates and transversal-related issues. It presents a critical vision of the state-of-the-art of the last 20 years, considering reference publications. The method is a documentary review that selects ten scientific articles from the last decade to discover deep trends. This documentary methodology differs from a systematic bibliographic review in that it allows selecting and delving deeper into the qualitative content of the articles. Thanks to the quality system implemented, the articles published in these journals included in thе WOS database ensure significant studies that ensure scientific contributions and discoveries in the field. The main results are ten recurring topic trends with the previous decade on language learning programs, evaluation, teaching strategies, communication and psychological approach, digital devices, teacher action, cognitive approach, speaking performance, motivation and instructional performance language. The major conclusions highlight emerging interdisciplinary approaches to different variables and the adaptive study of emerging technologies, such as AI, without great interest in linguistic or economic policy issues. However, searches on other academic platforms find a broader open debate for two decades with other contextual parameters about economic factors and language policy, such as the literacy of immigrants in L2 as a factor of social and economic interest, the formal programming of a second language in institutions to obtain employment, especially in the professional framework of international mobility. This means that the WOS database collects general trends in this investigated topic. However, it only partially collects the breadth of scientific interest generated as a result of the needs of the socio-economic context.
Keywords: research trends; performance; second language; learning; documentary review